(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Jason, the hero who stole the Golden Fleece, died abandoned by all, crushed by a beam from the ship that had carried him across the world. In this theatrical text, we encounter Jason, a hero turned opportunist who used his intelligence to seduce friends and lovers into serving his ambitious desire to become someone important, to secure for himself a place in the illuminated sun. This Jason can be read as a prototype of the conquering masculinity that characterizes modernity. Meanwhile, the more he tries to assert himself as a conqueror, the more patiently the Earth exacts its tribute.